The feasibility of using sediments from the Theewaterskloof, Greater Brandvlei and Waterzicht Dams as construction materials - Dorfling, Johannes Adolf (Stellenbosch : Stellenbosch University, 2019)
Thesis (MEng)--Stellenbosch University, 2019.